Tipologi Permukiman Desa Wisata di Indonesia - Salouw, Elvis (Sodality: Jurnal Sosiologi Pedesaan, 2022)
As a fast-growing industry sector, tourism has become an essential economic basis for villages. Law No 6 of 2014 has broadened the opportunity for villages to develop. A tourism village is considered one of the community empowerment options that can improve the economy and the village's development. Moreover, with all their uniqueness, tourism villages are also regarded as capable of eliminating urbanization's negative impact. Of 83.820 villages in Indonesia, 2% of them are tourism villages. This study took a sample of 55 tourism villages selected by the purposive sampling method and then described the sample based on five typologies, namely the settlement configuration, the classification of the village, the accessibility, the tourist attraction, and the category of the tourism village. The data used in the study were collected from various sources, specifically, those taken from official documents, credible websites, and previous studies to describe the typology owned by villages to become fast-growing tourism villages. The results show that, generally, tourist villages in Indonesia are dominated by rural tourism villages; however, urban tourism villages have a faster development. This study also points out the determining aspect of tourist village development.